Orthodontic treatment in class II malocclusion: case report - Pawinru, Ardiansyah S. (Hasanuddin University, 2020)
Objective: A male patient 23 years, 10 months with a Class II skeletal malocclusion, n class II subdivision dental-malocclussion, included openbite, overbite –6 mm, overjet 8 mm, agenesis of 41, mandibular midline shift to the right, deep palate, mandibular rectognathi and mild crowding of mandibular. Methods: Treatment was extraction of maxillary first premolar with a fixed appliance combined with Class II elastics and box elastic. After 2 years of treatment, correction of the openbite and overjet, lower anterior crowding were achieved. The treatment still continued. Results: The retention of post treatment with camouflage treatment is needed and takes a long time because some cases is reported be relapse very frequently, some literature suggests the use of permanent retention in openbite cases.Conclusion: Long retention is required for the stability of the treatment results.